ASSESSING MINORITY LANGUAGE IN THE SOUTH SULAWESI PROVINCE: LIMOLA LANGUAGE - Budiono, Satwiko; Jaya, Taufan (Paradigma: Jurnal Kajian Budaya, 2024)
The Limola language is a minority language spoken in South Sulawesi Province. Based on the number of speakers, which ranges between 100 and 600, the Limola language is at risk. This situation underscores the urgent need for preservation efforts. One approach to preserving the language is by assessing its vitality. The assessment of the Limola language aims to evaluate its current status and identify factors contributing to its vitality. These findings will inform future language preservation strategies. The study employs a descriptive qualitative method, with data collection techniques including observation, interviews, and focus group discussions. Data analysis is based on UNESCO’s nine language vitality factors. The results indicate that Limola is classified as critically endangered, primarily because the To Limola community predominantly uses the Tae language for daily communication. The Limola language is mainly spoken by middle-aged and older generations, with limited documentation available. This highlights the urgent need for written resources as part of preventive measures to avoid its extinction.